2016
DOI: 10.17159/2413-3108/2016/v0n57a1241
|View full text |Cite
|
Sign up to set email alerts
|

'Darker shades of blue': A comparison of three decades of South African Police Service culture

Abstract: Research on police has long recognised the importance of police culture in shaping officials' attitudes to work. In the decades since the early

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Research by Steyn & Mkhize (2016) has revealed a strong sense of isolation and cynicism amongst SAPS officers, linked to a lack of trust in and connection with members of the public and the communities they serve. Yet, citizen surveys in South Africa continue to flag crime as one of the top three priorities for government to address (Afrobarometer 2015).…”
Section: Democracy As Rights Rights As Licensementioning
confidence: 99%
“…Research by Steyn & Mkhize (2016) has revealed a strong sense of isolation and cynicism amongst SAPS officers, linked to a lack of trust in and connection with members of the public and the communities they serve. Yet, citizen surveys in South Africa continue to flag crime as one of the top three priorities for government to address (Afrobarometer 2015).…”
Section: Democracy As Rights Rights As Licensementioning
confidence: 99%
“…Over the next nine years of police service (Van Maanen and Manning's metamorphosis-stage of police culture socialisation) these attitudes were fortified and reinforced. 22 Steyn, Bell and De Vries made use of the same survey instrument to compare the attitudes of new SAPS recruits with those of recruits at the Justice Institute of British Columbia (JIBC) Police Academy. The study found that both new SAPS and JIBC police recruits had a shared affinity for police solidarity, but that while most SAPS recruits showed characteristics of isolation and cynicism, only half the JIBC recruits did.…”
Section: Research On Themes Of Solidarity Isolation and Cynicismmentioning
confidence: 99%
“…25 The PCSICQ is a composite measure consisting of three subscales, with 10 items per scale. Police culture cynicism coping theme subscale items [21] Most people lie when answering questions posed by police officials [22] Most people do not hesitate to go out of their way to help someone in trouble [23] Most people are untrustworthy and dishonest [24] Most people would steal if they knew they would not get caught [25] Most people respect the authority of police officials [26] Most people lack the proper level of respect for police officials A pilot study was conducted in December 2004 among 100 SAPS functional police officials stationed in the city of Durban, South Africa. Factor analysis identified nine factors, of which four met the latent root criterion (also known as the eigenvalue-one criterion or the Kaiser criterion).…”
Section: Outcome Variablesmentioning
confidence: 99%